Convergence culture: an analysis based on bibliometric indicators of production, citation and relational co-citation of authors in the Web of Science database (2008-2021) - Castanha, Rafael Gutierres [UNESP]; Santos Junior, Edmilson Alves dos; Tolare, Jessica Beatriz [UNESP] (Univ Federal Rio Grande Sul, Fac Biblioteconomia & Comunicacao, 2023)
This research analyzes the scientific production related to convergence culture through bibliometric indicators of production, citation and relational co-citation. Specifically, it evaluates scientific production using production and citation indicators, and characterizes the main influencers on the recovered work through the analysis of co-citation between authors. For this, it searches for the term convergence culture in the Web of Science database and evaluates the production of articles over the years together with the citations received and reveals, through the analysis of co-citation between authors, the main influencers on the retrieved work. To analyze the co-citations, it uses the concept of diachronic recitations of authors per document to build the intellectual structure of the domain in question. As a result, it presents a low productivity of articles close to saturation, 34% of the articles without citations received and with a clear deceleration of citations per article. It illustrates that the intellectual structure of the theme is composed of 46 authors most cited in the entire work, with emphasis on Henry Jenkins, Scolari, Williams, Bruns, Couldry, Deuze, Carpentier and Andrejevier. It concludes with low productivity on the subject and with strong influences from the pioneer Henry Jenkins, who is the most cited, recited and co-cited author among all cited authors.
Keywords: analysis of co-citation among authors; bibliometrics; convergence culture; scientific production